Human Walking in Virtual Environments 2013
DOI: 10.1007/978-1-4419-8432-6_12
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Rendering of Walking Over Virtual Grounds

Abstract: The addition of multimodal feedback during navigation in a virtual environment is fundamental when aiming at fully immersive and realistic simulations. Several visual, acoustic, haptic or vibrotactile perceptual cues can be generated when walking over a ground surface. Such sensory feedback can provide crucial and varied information regarding either the ground material itself, the properties of the ground surface such as slope or elasticity, the surrounding environment, the specificities of the foot-floor inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 83 publications
1
9
0
Order By: Relevance
“…Furthermore, non-directional tactile cues have been shown to provide some self-motion cues (Terziman et al, 2012;Feng et al, 2016) while directional cues can be used to aid directional guidance, e.g., by using higher density grids of vibrotactors under the foot sole (Velázquez et al, 2012). In some studies, vibration and audio cues have been studied in concert and showed cross-modal benefits in ground-surface perception (Marchal et al, 2013) and selfmotion perception (vection) (Riecke et al, 2009).…”
Section: Haptic Feedback To Locations Other Than the Handsmentioning
confidence: 99%
“…Furthermore, non-directional tactile cues have been shown to provide some self-motion cues (Terziman et al, 2012;Feng et al, 2016) while directional cues can be used to aid directional guidance, e.g., by using higher density grids of vibrotactors under the foot sole (Velázquez et al, 2012). In some studies, vibration and audio cues have been studied in concert and showed cross-modal benefits in ground-surface perception (Marchal et al, 2013) and selfmotion perception (vection) (Riecke et al, 2009).…”
Section: Haptic Feedback To Locations Other Than the Handsmentioning
confidence: 99%
“…Particularly, the somatosensory pressure receptors inform the walker about physical contact with objects on the path (Waller and Hodgson 2013). Haptic feedback is intended to provide such information by reproducing forces, movements, and other cutaneous sensations felt via the sense of touch (Marchal et al 2013). In a manner similar to Lindeman et al (1999), we distinguish between two approaches for supplying individuals with cutaneous information during virtual walking.…”
Section: Haptic Feedbackmentioning
confidence: 99%
“…With respect to active-haptic feedback, Marchal et al (2013) stated that the addition of even low-fidelity tactile feedback may increase the sensation of presence in an audiovisual virtual environment. Along similar lines, Srinivasan and Basdogan (1997) suggested that the potential gains of adding such tactile feedback may be larger than improving the quality of the feedback delivered to an existing modality (e.g., the visual display).…”
Section: Haptic Feedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…Among others, presence is increased through high realism in the VE [28], which can be achieved through multimodal stimuli [25], e.g. by applying physical laws, environmental sounds, haptic feedback [37] and the correct rendering of walking over virtual grounds [42]. As, by definition, mindful practice increases the awareness of oneself and the surrounding of the present moment [32], low presence through mismatches of visual, tactile and auditory cues could distract while high presence could support attention to body and mind.…”
Section: Introductionmentioning
confidence: 99%